Development of a peptide drug restoring AMPK and adipose tissue functionality in cancer cachexia - Ji, Honglei; Englmaier, Felix; Morigny, Pauline; Giroud, Maude; Gräsle, Pamina; Brings, Sebastian; Szendrödi, Julia; Berriel Diaz, Mauricio; Plettenburg, Oliver; Herzig, Stephan; Rohm, Maria (Molecular therapy, 2023)
Cancer cachexia is a severe systemic wasting disease that negatively affects quality of life and survival in patients with cancer. To date, treating cancer cachexia is still a major unmet clinical need. We recently discovered the destabilization of the AMP-activated protein kinase (AMPK) complex in adipose tissue as a key event in cachexia-related adipose tissue dysfunction and developed an adeno-associated virus (AAV)-based approach to prevent AMPK degradation and prolong cachexia-free survival. Here, we show the development and optimization of a prototypic peptide, Pen-X-ACIP, where the AMPK-stabilizing peptide ACIP is fused to the cell-penetrating peptide moiety penetratin via a propargylic glycine linker to enable late-stage functionalization using click chemistry. ...